El cuidado desde una perspectiva psicosocial - Begoña Carbelo Baquero; Marta Romero Llort; Francisca Casas Martínez; Teresa Ruiz Ureña; Sonsoles Rodríguez de la Parra (Universidad de Alicante, 1997)
This work intends to make a reflexive analysis of the different discipline contributions in the psychosocial projection of the nurse cares. The psychosocial nursing is somewhat more than some psychological knowledge for professional of nursing ; the Psychosocial Sciences permit us to approach to the human being from holistic point of view. The different schools or trends in nursing, deepen in the care of the human being and of the environment as essential components of the health ; from these lines are analyzed the different psychosocial aspects that permit to guide the nurse actions toward the self-care of patients and their family, and to describe, to explain and to understand the human behavior not alone in the disease but in aspects as quality of life, adjustment to the environment and the resources development to face the different situations and to reach the welfare.